PENGARUH LIVE STREAMING DAN AFFILIATE MARKETING TERHADAP KEPUTUSAN PEMBELIAN MILENIAL PENGGUNA SHOPEE SUKABUMI - sari, Novita; Haryanto, Friyadi; Slamet Rachmadi, Lucky (PT. ABIG RIZKY PUBLISHER, 2026)
This study aims to analyze the influence of livestreaming and affiliate marketing on purchasing decisions on the Shopee application, with a case study of the Millennial Generation in Sukabumi City. The research employs a quantitative approach with an associative method to examine the relationships and effects among variables. Data were collected through questionnaires distributed to 100 respondents who are active Shopee users and have made purchases via the Shopee Live feature or affiliate links. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The results indicate that, partially, livestreaming has a positive and significant effect on purchasing decisions. This suggests that real-time interaction, product demonstrations, and two-way communication in livestreaming can enhance consumer trust and purchase intention. In addition, affiliate marketing is also proven to have a positive and significant effect on purchasing decisions, reflecting the strong role of recommendations from content creators or affiliates in shaping consumer perceptions and confidence. Simultaneously, livestreaming and affiliate marketing have a significant effect on purchasing decisions, with a coefficient of determination of 69.8%. This means that both variables are able to explain a large proportion of the variance in consumer purchasing decisions. These findings confirm that interactive and recommendation-based digital marketing strategies play a strategic role in encouraging consumer purchasing decisions on e-commerce platforms such as Shopee.